Does Ethical Climate, Rewards, and Protections Matter for Individual Intention to Blow The Whistle? - Nova Trinita Sihombing; Fitri Ahmad Kurniawan (Master of Accounting Universitas Trunojoyo Madura, 2021)
This paper aims to examine factors that can predict an individual intention to take whistleblowing action. This study examines the effect of ethical climate-egoism, ethical climate-benevolence, ethical climate-principle, rewards, and legal protection of whistleblower on the intention of Batam public procurement agency employees to do whistleblowing. This study used a quantitative approach with questionnaire data collected technique using census sampling as a sampling method. Partial Least Square (PLS) via SmartPLS 3.0 program is used as the analytical method to running the data. This study analyzes all civil servants in The Batam Public Procurement Agency. The results show that ethical climate-principle and legal protection of whistleblower affect the intention to do whistleblowing significantly. While the ethical climate-egoism, ethical climate-benevolence, and giving rewards to whistleblower showed that the results did not affect the intention of Batam Public Procurement agency employees to do whistleblowing significantly.